Um mapeamento de pesquisas a respeito do estudo de álgebra nos anos finais do Ensino Fundamental e Ensino Médio (2008 – 2017) - Borges, Maria Elizabeth de Oliveira (2018)
The present study, with a qualitative bibliographical approach, aims to present the state of the art of academic research whose subjects involve the teaching and learning processes of Algebra in the final years of Elementary and Secondary Education, published in the period between 2008 and 2017. The corpus of analysis consists of 42 researches obtained, mainly, in digital media, from the following bases: Bank of Thesis and dissertations of the Coordination of Higher Level Personnel Improvement - CAPES and repositories of theses and dissertations of the Programs post graduate. In order to compose the analysis data, each work was recorded, based, in particular, its bibliographic data and abstracts. Among the main results obtained, we highlight that of the 42 surveys collected, three were PhD’s theses and 39 were Master's dissertations. The mapping of these surveys revealed the quantity of productions per higher education institution, by regions and by post-graduate programs. The analysis of the productions was done through the categories: Algebraic Language and Thinking; Relation between Algebra / Arithmetic / Geometry; Multiple Representations; Materials / didactic resources; Conceptions / Knowledge; Teaching Methodology and Pedagogical Practice. We could observe that research focuses more on students in the final years of Elementary School than on high school and continues to point out the difficulties of students in constructing algebraic knowledge, particularly those involving variability. The few works that deal with teachers point to their dissatisfaction with the lack of connection between the initial formation and the practice in the classroom, besides divergences regarding their knowledge for the teaching of Algebra. Of the analyzed works few discuss the official documents or textbooks regarding what they propose for the teaching of algebra. In addition, in the works that deal with specific contents it is noticed that some are more worked, as is the case of equations of first and second degrees, while others are not treated. Thus, for a better understanding of the state of Algebra teaching and learning, it is necessary to develop research that addresses the teaching and/or learning of other algebraic subjects in Basic Education, as well as in-depth analyzes of the proposed curriculum for teaching arranged in documents officers and/or textbooks, as well as to investigate the knowledge necessary for teachers to be able to teach this subject, among other possible topics